MOBILE WEB BASED SCHOOL INFORMATION SYSTEM GOVERNANCE - Riyanto, Nila Agus; Hamid, Abdul; Maryati, Ulfah Dina (JLCEdu (Journal of Learning and Character Education), 2022)
Schools are one of the basic needs of society in order to improve human resources through academic education and other supporting education. Through schools, people can study the development of education by utilizing the development of technology and information which is increasingly easy to obtain. Currently schools are trying to become institutions that are able to serve the community well, especially in terms of conveying information to the community. However, so far information is still done manually, such as pasting on announcement boards, circulars distributed to students. Along with the rapid development of technology and information, the researchers aim to create a mobile web-based school information system at MTS Ma'arif so that all information can be accessed easily. Researchers designed and realized a mobile web-based school information system using the PHP programming language and MySQL database. The use of the mobile web in competency development and school quality is the right thing because the mobile web is a very informative and dynamic medium to add insight in finding educational information. The implementation in this study can be accessed anytime and anywhere via the internet. The mobile web can make it easier for schools to convey information and promotional processes that have so far been done manually.